THE EFFECTIVENESS OF MAHKOTA WITNESSES (KROON GETUIDE) EVIDENCE ON NARCOTICS ABUSE - Yasmirah Mandasari Saragih; Muhammad Ridwan Lubis (International Journal of Law Reconstruction, 2021)
The use of Mahkota witnesses in Indonesia is still a matter of debate today, both among practitioners and academics, because there is no legal certainty regarding the use of this Mahkota witness. The research method uses juridical normative, the results obtained state that the effectiveness of the presence of Mahkota witnesses is to complete the minimum requirements for evidence to prove someone guilty. Where in the case of narcotics abuse, the lack of evidence found can facilitate the judicial process, the Mahkota witness is used to complete the truth to be revealed or material truth. The Mahkota witness does not affect the severity or lightness of the crime, but its usefulness is as a matter of convincing about the defendant's guilt or whether or not a narcotics abuse is proven. The testimony of the Mahkota witness has the power of proof if it is declared valid as a witness, there is no objection from the defendant's legal adviser regarding the presence of the Mahkota witness and the statement is stated before the court which has been sworn in beforehand and the information given is in accordance with the testimony given by other witnesses or tools other evidence so as to prove the defendant's guilt.